7.9k views
2 votes
Use logical equivalences (not a truth table) to reduce p → (q − p) to a tautology t. In other words, you should transform p → (q − p) into an equivalent statement, then transform that into another equivalent statement, and so on, until you arrive at a tautology. Your solution should look something like this: p → (q − p) = statement = statement = . . . . ... = t. (Note: the symbol = is technically the same as H. It's just easier to use = , because can easily be confused as being part of the logical statement you're transforming).

User Shiun
by
5.3k points

1 Answer

2 votes

Answer:

The statement
p\rightarrow (q\rightarrow p) is a tautology.


p\rightarrow (q\rightarrow p)\equiv \lnot p\lor (q\rightarrow p) \equiv \lnot p\lor (\lnot q\lor p) \equiv (p\lor \lnot p) \lor \lnot q \equiv T \lor \lnot q \equiv T

Explanation:

We have the following statement:


p\rightarrow (q\rightarrow p)

To reduce the statement to a tautology we need to use the table of logical equivalences as follows:


p\rightarrow (q\rightarrow p)\equiv


\equiv \lnot p\lor (q\rightarrow p) by the the logical equivalence involving conditional statement.


\equiv \lnot p\lor (\lnot q\lor p) by the the logical equivalence involving conditional statement.


\equiv (p\lor \lnot p) \lor \lnot q by the Associative law.


\equiv T \lor \lnot q by the Negation law.


\equiv T by the Domination law.

Use logical equivalences (not a truth table) to reduce p → (q − p) to a tautology-example-1
User Kishore Mohan
by
4.8k points